The Implications of IDX Regulation (Kep-00027/BEI/03-2020) for Audit Delay: Before, During, and After Pandemic - Dian Indri Purnamasari; Hari Kusuma Satria Negara; Sri Hastuti; Puji Handayani Kasih; Isnu Angga Winata (Applied Quantitative Analysis, 2026)
Audits play a crucial role in ensuring the reliability of financial statements for stakeholders. However, audit delay may undermine information quality, reduce market confidence, and disrupt decision-making. To address these challenges, the Indonesia Stock Exchange (IDX) issued Regulation Kep-00027/BEI/03-2020, which relaxed reporting deadlines. Nevertheless, limited studies have examined the effectiveness of this regulation across the periods before, during, and after the COVID-19 pandemic. This study aims to analyze the impact of IDX regulation on audit delay by considering auditee characteristics, auditor characteristics, and external factors, with audit tenure as a moderating variable and COVID-19 as a control variable. The research employs secondary data from financial statements of IDX-listed companies during 2016–2024. Ordinary Least Squares (OLS) regression and moderation analysis are applied to evaluate both direct effects of independent variables on audit delay and interaction effects with audit tenure. The findings reveal that the relaxation policy helped reduce audit delay during the pandemic, although its effectiveness varied depending on firm size, profitability, ownership, and operational complexity. Audit tenure demonstrated a dual role: facilitating faster audits for complex firms due to accumulated auditor knowledge, yet potentially compromising independence when the relationship extended excessively. These results contribute to regulatory discourse by highlighting the need for adaptive reporting policies and provide practical insights for companies and auditors in balancing audit efficiency with independence and quality.